PENERAPAN PROGRAM SATUAN PENDIDIKAN AMAN BENCANA (SPAB) DI SDN 09 BEROK NIPAH KOTA PADANG - Maharani, Maharani; Wau, Witarni; Putri, Oktri Dwi; Putra Ulni, Arie Zella (Jurnal Spasial, 2024)
This study is motivated by the performance of local disaster management institutions. Padang City is a way to reduce flood disaster management. Where is the body Local Disaster Management Has Duties and Roles With the potential threat of flood disasters, there is no worrying threat. Research Objectives to Examine Performance Measuring Padang City Regional Disaster is a way to reduce flood disaster management. This research method uses qualitative research methods. Research Shows the performance of the Local Disaster Management Agency in Padang City When reducing flood disaster management, implementation of implementation Standard operations, programs, and guidelines are carried out BPBD Padang City meets the needs of our community. But still there Some obstacles from BPBD in Padang City in reducing the reduction Flood Disaster, I.E.: Limited Human Resources, Still Low Community awareness and participation in disaster management programs Flood and inadequate facilities and infrastructure that have been practiced BPBD Padang City, e.g. Work in reducing flood disaster managementSame as the socialization of related institutions and communities, namely We can conclude that the performance of the Disaster Management Agency in Padang City can be achieved Regarding implementation, programs and guidelines are implemented following the appropriate steps. The steps that emerge.